First Molecular Characterization of Bovine Leukemia Virus Infections in the Caribbean - Yang, Yi; Kelly, Patrick John; Bai, Jianfa; Zhang, Rong; Wang, Chengming (My University, 2016)
Bovine leukemia virus (BLV) is a retrovirus that causes enzootic bovine leucosis. To investigate the presence and genetic variability of BLV in the Caribbean for the first time, we preformed fluorescence resonance energy transfer (FRET)-PCR for the pol of BLV on DNA from whole blood of cattle from Dominica, Montserrat, Nevis and St. Kitts. Standard PCRs with primers for the env were used for phylogenetic analysis of BLV in positive animals. We found FRET-PCR positive cattle (12.6%, 41/325) on Dominica (5.2%; 4/77) and St. Kitts (19.2%; 37/193) but not on Montserrat (0%, 0/12) or Nevis (0%, 0/43). Positive animals were cows on farms where animals were raised intensively. Phylogenetic analysis using the neighbor-joining (NJ) method on partial and full-length env sequences obtained for strains from Dominica (n = 2) and St. Kitts (n = 5) and those available in GenBank (n = 90) (genotypes 1–10) revealed the Caribbean strains belonged to genotype 1 (98–100% sequence homology). Ours is the first molecular characterization of BLV infections in the Caribbean and the first description of genotype 1 in the region.
Citation: Yang Y, Kelly PJ, Bai J, Zhang R, Wang C (2016) First Molecular Characterization of Bovine Leukemia Virus Infections in the Caribbean. PLoS ONE 11(12): e0168379. doi:10.1371/journal.pone.0168379
Keywords: Sequence alignment; Caribbean; Cattle; Phylogenetic analysis; Nucleotide sequencing; Protein sequencing